2007
DOI: 10.1017/s1047951107001138
|View full text |Cite
|
Sign up to set email alerts
|

The nomenclature, definition and classification of cardiac structures in the setting of heterotaxy

Abstract: In 2000, The International Nomenclature Committee for Pediatric and Congenital Heart Disease was established. This committee eventually evolved into the International Society for Nomenclature of Paediatric and Congenital Heart Disease. The working component of this international nomenclature society has been The International Working Group for Mapping and Coding of Nomenclatures for Paediatric and Congenital Heart Disease, also known as the Nomenclature Working Group. The Nomenclature Working Group created the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
256
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(272 citation statements)
references
References 40 publications
2
256
0
9
Order By: Relevance
“…Classifi cation of these defects is complicated because diff erent specialists tend to use diff erent defi nitions for SA and heterotaxy. [4][5][6][7][8] Some clinicians interchange the terms "situs ambiguus" and "heterotaxy"; however, cardiologists defi ne heterotaxy as a subset of SA with specifi c congenital heart defects (eg, common atrium, levo-transposition of great arteries). Geneticists have expanded the cardiology definition to include combinations of abdominal defects (eg, asplenia, polysplenia) or vascular defects (eg, interrupted inferior vena cava).…”
mentioning
confidence: 99%
“…Classifi cation of these defects is complicated because diff erent specialists tend to use diff erent defi nitions for SA and heterotaxy. [4][5][6][7][8] Some clinicians interchange the terms "situs ambiguus" and "heterotaxy"; however, cardiologists defi ne heterotaxy as a subset of SA with specifi c congenital heart defects (eg, common atrium, levo-transposition of great arteries). Geneticists have expanded the cardiology definition to include combinations of abdominal defects (eg, asplenia, polysplenia) or vascular defects (eg, interrupted inferior vena cava).…”
mentioning
confidence: 99%
“…We propose that the evidence now supports a more effective description of splenic syndromes in terms of right or left isomerism, based ideally on knowledge of the morphology of the atrial appendages. If, however, the appendages are not visualized on imaging or at the time of cardiac surgery, the evidence at hand strongly supports the notion that the morphology of these structures can be inferred on the basis of associated congenital malformations (2,3).…”
mentioning
confidence: 70%
“…Studies have used different definitions and classification systems for heterotaxy [12,[78][79][80][81][82][83], despite standardisation efforts [84]. While some authors group situs inversus and situs ambiguous under the umbrella of heterotaxy [82], others believe it should be restricted to situs ambiguous only [2,81,83,84].…”
Section: Cardiac Managementmentioning
confidence: 99%
“…While some authors group situs inversus and situs ambiguous under the umbrella of heterotaxy [82], others believe it should be restricted to situs ambiguous only [2,81,83,84]. Using the latter definition, KENNEDY et al [83] reported that over 6% of PCD patients presented with heterotaxy.…”
Section: Cardiac Managementmentioning
confidence: 99%